Relationships between Women in Fay Weldon´s Novels - Kovaříková, Martina (Univerzita Pardubice, 2010)
This bachelor paper deals with relationships between women in the work of the British writer Fay Weldon. On the example of her novels Big Women and Worst Fears three women´s relationships are analyzed: mother - daughter, wife - lover and friend - friend. The work is focused on the development of these relations under the pressure of various circumstances. Further the attitude of the society towards women´s relationships is analyzed as well as the influence men have on them.
Vztahy mezi ženami v románech Fay Weldon
Keywords: britská próza; vztahy; ženy; Weldon, Fay; Anglická literatura; relationships; women; English literature